Validity and reliability of questionnaire items for the development of the green competency model among polytechnic lecturers in Malaysia using Rasch measurement model - M.Said, Salina; Hasan, Azman; Monzaid, Eza; Zaime, Adib Farhan (American Scientific Publishers, 2018)
The Questionnaire of Green Competency Model is developed to measure the green competency among Polytechnic lecturers based on knowledge, skills and self-effectiveness elements as well as their sub elements. The study was conducted to produce empirical data on the reliability and validity of the Green Competency Questionnaire using the Rasch Measurement Model. A survey was conducted in the Polytechnic Institution on 30 respondents including 15 third year students, 10 lecturers, four Head of Departmentsfrom engineering and non-engineering departments and one head of Training and Advanced Education unit. The reliability and validity of the Green Competency questionnaire were tested with the Rasch Measurement Model using the Winsteps software. In terms of item polarity, each item was able to contribute the measurement of green competency elements and their sub elements except two items since the PTMEA CORR has recorded in a zero index. Item fit analysis showed that four items need to be dropped. For largest standardized residual correlations analysis result, there were two items to be dropped but one of the item was eliminated from the previous diagnostic process. This means that from 99 items, there are seven items to be eliminated and they have been excluded from the item list in the questionnaire. This finding provides the validity and reliability of the Polytechnic Lecturers Green Competency Model questionnaire. The analysis of Rasch Measurement Model has proven that this questionnaire has a high degree of validity and reliability and can be used measuring the elements and sub elements of green competency model among Polytechnic lecturers.